Strategi Pengembangan Ekonomi Berdikari Di Pesantren Gontor Berbasis Pengelolaan Kopontren - syamsuri, syamsuri (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2020)
As an effort to create a community of civilization, pesantren is required to take an active role in the life of society universally, not only tafaqquh fi dien but also trying to create a buffer of pesantren independence one of which is a cooperation of pondok pesantren (kopontren) a guaranteed survival of the pesantren's lifetime. Since 90 years ago Gontor has become a pioneer in inspiring pesantren to be independent at Indonesia, the step begins with developing an economic enterprise independently. This article is trying to examine the concept of kopontren which is not same as the cooperations in general, from that concept the strategy of economic independence of pesantren will be revealed. By using case study research in Kopontren Gontor with data collection is triangulation method, finally this article found that the kopontren as the only center of economic activity, the kopontren become place for cadre development and entrepreneurship training for santri, and the kopontren have been able to improve economic prosperity of society around pesantren